GAGASAN PEMIDANAAN TERHADAP PELAKU KEJAHATAN PEMERKOSAAN MAYAT (NEKROFILIA) DALAM HUKUM POSITIF INDONESIA - Kowland Hawary; Dessy Artina; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Necrophilia is a disease (abnormality) in the form of sexually interested to get a body, people who have sex with a corpse, and an abnormal sense of interest in the body. Necrofilia is commonly referred to as Thanatophilia or Necrolagnia. It is an abnormality of desire in the human body because it is attracted to sex with dead bodies. Along with the times, many people are acting out of their nature. Where many irregularities occur from human behavior itself. One deviation from the nature itself has sexual irregularities performed by someone who has sexual disorders such as Pedofhilia, Zoofhilia, LGBT (Lesbian, Gay, bisexual and Transgender), necrophilia and others. In Indonesia, there is no legal arrangement against the perpetrators of sex necrophilia, so it takes an idea that can cause a deterrent effect on the perpetrators of rape crimes against the Corpse (necrophilia). The purpose of writing this thesis, namely first, to know the EAS against the crime perpetrators of the body rape (necrophilia) in the positive law of Indonesia. Second, knowing the idea of the EAS against the criminal perpetrators of the body rape (necrophilia) in the positive law of Indonesia. Thirdly, knowing the EAS against the criminal perpetrators of rape (necrophilia) in the positive law of Indonesia.From the results of the problem research there are three main things that can be concluded. First, the chapters in the Criminal Code and the Criminal Code of the Penal Code are not clearly set up directly about the imposition of the rapist or body but there are some proceeding inside the Criminal Code and the Criminal Code that directs the deed Can be sentenced. Secondly, the arrangement of rape against dead bodies has not yet been legally governing only chapters 285 and 286 The CRIMINAL code is more directed toward people who are still living are not people who have died/died so clearly the law governing A rapist against a deceased person, this is what causes confusion in the community about what rules should be worn or applied.Keywords: Necrophilia-Rape of the Dead-Crimes